PTU-150 Concordance between Endoscopic Ultrasound (EUS) and Positron Emission Tomography (PET) in the Staging of upper Gastrointestinal Cancer – a District General Experience. (4th June 2013) - Seenan, J P; Sadler, R; Stanley, A J; Paterson, S
Abstract : Introduction: Approximately 1700 patients/year are diagnosed with oesophageal or gastric cancer in Scotland. The Scottish Audit of Gastric and Oesophageal Cancer (SAGOC) previously reported under-staging of these cancers pre-operatively with curative surgery attempted too often. This resulted in incomplete resection and recurrence with a one year postoperative survival of only 53%. Increasing emphasis has therefore been placed on accurate pre-operative staging. Current guidelines advise multimodal staging with CT, EUS +/- laparoscopy if gastric involvement. Recently the use of PET staging has increased. We sought to establish the concordance between EUS and PET in the staging of upper GI cancer within a large district general hospital. Methods: A retrospective study was performed in patients with oesophageal or gastric cancer referred for multimodal staging with CT, EUS and PET between October 2008 and November 2011. Each case was reviewed at the local multi-disciplinary team (MDT) meeting. MDT outcome forms were collated and a casenote review performed. Baseline demographics, tumour characteristics and TNM staging was recorded. Results: 59 patients (45 male) were referred for both EUS and PET. The majority had adenocarcinoma (49/59, 83.1%) with 9 squamous carcinomas (15.3%) and 1 carcinoid (1.7%). A malignant stricture prevented EUS in 3 patients while in 3 patients CT-PET revealed metastatic disease and EUS was cancelled. 53 patients (40 male) underwent staging with both modalities. Concordance of N staging between EUS and PET was 75.9%. In 13/53 patients EUS altered prior PET staging, upstaging from N0 to N1 in 12/13 (91.4%). In patients undergoing EUS-FNA (10 mediastinal, 1 sub-diaphragmatic), 2/11 (18.2%) patients were found to have malignant lymphadenopathy affecting PET negative nodes while in 1 patients a PET positive node was found to be benign. EUS was more accurate in predicting resection N stage (65%) than PET (38.9%) with both tending to underestimate. In patients with T3 disease there was a significant difference in N staging between patients undergoing resection and those treated palliatively (p < 0.05). Conclusion: Nodal staging by EUS and PET differs in a significant proportion of patients undergoing pre-operative work-up for upper GI cancer. In the majority of cases PET underestimates nodal staging. However, technical difficulties may preclude EUS while the finding of distant metastases at PET prior to EUS may prevent unnecessary investigations. CT and EUS remain the mainstay of pre-operative staging in oesophageal and gastric cancers but PET is a useful adjunct. Disclosure of Interest: None Declared